History teaching, ICTs and flipped classroom: : discussing pandemics - Alberto, Márcia de Souza Oliveira Paes Leme; Medeiros, Lílian Gobbi Dutra; Felício, Cínthia Maria; Carvalho, Marco Antônio de; da Silva Santiago, Léia Adriana (Revista Labor, 2024)
This paper aims to report a pedagogical practice, from the use of active methodologies applied in history classes, through Information and Communication Technologies (ICTs), carried out in a class of the Technician Course in Informatics Integrated to High School of a Federal Institution of Education. This is a descriptive and bibliographic study, with a qualitative approach. It is an experience report, developed from the didactic sequences of Zabala (1998). In this period of social isolation, caused by the covid-19 pandemic, it becomes relevant to address issues related to teaching and learning processes through ICTs, considering that the virtual environment has been the alternative adopted by educational institutions to teach their classes. Taking into consideration the results presented in the text, we realized that active methodologies and the use of ICTs might become excellent tools at the service of education, when well-planned and articulated with proposals aimed at the autonomy and protagonism of students.